2012
DOI: 10.1242/jcs.100032
|View full text |Cite
|
Sign up to set email alerts
|

Supervillin couples myosin-dependent contractility to podosomes and enables their turnover

Abstract: SummaryPodosomes are actin-rich adhesion and invasion structures. Especially in macrophages, podosomes exist in two subpopulations, large precursors at the cell periphery and smaller podosomes (successors) in the cell interior. To date, the mechanisms that differentially regulate these subpopulations are largely unknown. Here, we show that the membrane-associated protein supervillin localizes preferentially to successor podosomes and becomes enriched at precursors immediately before their dissolution. Consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(154 citation statements)
references
References 76 publications
14
135
0
5
Order By: Relevance
“…S6) has been reported in previous studies using magnetic twisting cytometry (58). This effect is not likely due to a low expression level of myosin IIA in macrophages (59,60). Instead, the different expression levels of nesprin 1 and 2, SUN1, vimentin, plectin, and lamin A/C in macrophages compared to neutrophils and monocytes (61,62), as well as a more adherent nature of macrophages that reside normally in the tissue, might play a role.…”
Section: Discussionsupporting
confidence: 60%
“…S6) has been reported in previous studies using magnetic twisting cytometry (58). This effect is not likely due to a low expression level of myosin IIA in macrophages (59,60). Instead, the different expression levels of nesprin 1 and 2, SUN1, vimentin, plectin, and lamin A/C in macrophages compared to neutrophils and monocytes (61,62), as well as a more adherent nature of macrophages that reside normally in the tissue, might play a role.…”
Section: Discussionsupporting
confidence: 60%
“…Likewise, we found that ECM rigidity controls the activity, but not the formation of, invadopodia puncta . In addition, several studies have shown that myosin-mediated contractility can induce the turnover of podosomes (Bhuwania et al, 2012;van Helden et al, 2008). Other studies have directly examined the role of adhesion molecules, including integrins and downstream adhesion components.…”
Section: Regulation Of Invadopodia and Podosomes By Adhesion Protein mentioning
confidence: 99%
“…Actin retrograde motion is likely to be driven by the polymerization of its filaments (Henson et al, 1999). Additionally, the actin-associated molecular motor myosin II has been found to contribute to actin flow by exerting contractile forces on actin filaments (Vicente-Manzanares et al, 2009;Betapudi, 2010;Arii et al, 2010;Bhuwania et al, 2012). Nonmuscle myosin IIA is the dominantly expressed isoform of myosin II in T cells (Jacobelli et al, 2004).…”
Section: Interplay Between Actin and Myosin Iia In Tcr Signalingmentioning
confidence: 99%